A regarded self : Caribbean womanhood and the ethics of disorderly being - Glover, Kaiama L., 1972- (Duke University Press, 2021)
"In A Regarded Self Kaiama L. Glover champions unruly female protagonists who adamantly refuse the constraints of coercive communities. Reading novels by Marie Chauvet, Maryse Condé, René Depestre, Marlon James, and Jamaica Kincaid, Glover shows how these authors' women characters enact practices of freedom that privilege the self in ways unmediated and unrestricted by group affiliation. The women of these texts offend, disturb, and reorder the world around them. They challenge the primacy of the community over the individual and propose provocative forms of subjecthood. Highlighting the style and the stakes of these women's radical ethics of self-regard, Glover reframes Caribbean literary studies in ways that critique the moral principles, politicized perspectives, and established critical frameworks that so often govern contemporary reading practices. She asks readers and critics of postcolonial literature to question their own gendered expectations and to embrace less constrictive modes of theorization"--Publisher's description.